2020
DOI: 10.1186/s13063-020-4193-7
|View full text |Cite
|
Sign up to set email alerts
|

Ginger in patients with active ulcerative colitis: a study protocol for a randomized controlled trial

Abstract: Background: As a lifetime disorder, ulcerative colitis (UC) is an inflammatory bowel disease (IBD) that affects quality of life and also demands long-term interventions. In spite of considerable side effects and sometimes restricted uses, efficient medications are available for UC treatment. Some in vitro and in vivo examinations have correspondingly introduced ginger and its active components with antioxidant, anti-inflammatory, and anti-ulcerative properties. Therefore, this trial aims to evaluate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…It was shown that 6G significantly ameliorated inflammatory and oxidative process 48 . In IBD models, it was indicated that 6G suppressed ROS and NO expression due to NF‐kB restraint 16,37 . 6G also diminished NO, COX‐2, PGE2, TNF‐α, IL‐2, IL‐4, IL‐5, IL‐12, IL‐17, and IL‐1β.…”
Section: Clinical In Vivo and In Vitro Evidence Of Therapeutic Effects Of Ginger Preparations In Ibdmentioning
confidence: 99%
See 3 more Smart Citations
“…It was shown that 6G significantly ameliorated inflammatory and oxidative process 48 . In IBD models, it was indicated that 6G suppressed ROS and NO expression due to NF‐kB restraint 16,37 . 6G also diminished NO, COX‐2, PGE2, TNF‐α, IL‐2, IL‐4, IL‐5, IL‐12, IL‐17, and IL‐1β.…”
Section: Clinical In Vivo and In Vitro Evidence Of Therapeutic Effects Of Ginger Preparations In Ibdmentioning
confidence: 99%
“…Ginger exhibited successful therapeutic effects when administered via different routes in experimental animal models, that is, by oral gavage 36 or intraperitoneal 37 administration. In addition, orally prescribed ginger capsules in human clinical trials showed that daily treatment with ginger powder proved beneficial for UC management 16,41 . Nanomedicine drug delivery systems are recent developments of new selectively polymeric carriers and novel synthetic approaches for enhancing beneficial physicochemical properties and penetration of medicines in IBD.…”
Section: Ginger Drug Delivery In Ibdmentioning
confidence: 99%
See 2 more Smart Citations
“…Another double blind, randomized, controlled study indicating the efficacy of ginger capsule in UC patients was performed. The down-regulation of inflammatory mediators and high sensitivity of C-reactive protein (hs-CRP) showed protective effect in treatment of UC and can be given up to 3 g/kg (Shayesteh et al 2020 ).…”
Section: Safety Concerns Of Herbal Products Used In Ucmentioning
confidence: 99%